Pengaruh Harga Produk dan Kualitas Produk terhadap Kepuasan Pelanggan Kedai Mimi - Jaelani, Muhamad; Fitriani, Risma; Fatwa, Muhammad Adi (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
With so many shop businesses in Indonesia, it requires every shop business to be able to compete by providing satisfaction to its consumers. Two of the factors that have a positive influence on consumer satisfaction are product price and product quality. Therefore, the purpose of this study is to test whether product price and product quality have a positive effect on Kedai Mimi consumer satisfaction. This study uses a quantitative approach with validity tests and reliability tests as a measuring tool for research indicators, as well as classical assumption tests, and multiple linear regression assisted by SPSS software to analyze the relationship between the variables studied. The results showed that product prices and product quality had a positive effect on consumer satisfaction at Mimi Shop by 69.2%.